Reducing enrollment disparities for prospective racially minoritized graduate students through financial aid: evidence from an online survey experiment in the U.S. - Templeton, Da'Shay; Korchagin, Ruslan (Frontiers in Education, 2025)
IntroductionRacially minoritized students remain underrepresented in U.S. graduate education despite persistent gaps in enrollment. While academic predictors of success are well documented, less is known about enrollment predictors, particularly the influence of financial aid and learning modalities.MethodsThis study employed a mixed factorial design using a nationally distributed online survey with quota sampling. The sample consisted of bachelor's degree holders who identified as Black, Latin*, or Native American (N = 1,067). Participants were randomly assigned to one of six experimental conditions that varied by aid status (aid vs. no aid) and learning modality (online, hybrid, in-person). Enrollment intentions, beliefs about graduate outcomes, and preferences for full- vs. part-time study were measured.ResultsFinancial aid significantly increased the likelihood of enrollment, preference for full-time study, and belief that graduate education improves job prospects. In contrast, learning modality (online, hybrid, in-person) showed no significant effect on enrollment intentions or perceived outcomes. Aid status did not significantly affect expectations of salary improvement or reliance on loans.DiscussionThe findings underscore the pivotal role of financial support in reducing structural barriers to graduate education for racially minoritized students. Expanding need-based aid, simplifying application processes, and increasing transparency about graduate outcomes are recommended policy strategies to improve equity in access to advanced degrees.